1986
DOI: 10.1042/bj2350847
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of rat heart cytosol 5′-nucleotidase by adenylate energy charge

Abstract: A 5'-nucleotidase (EC 3.1.3.5) was highly purified from the soluble fraction of rat heart. The preparation appeared homogeneous by the criterion of polyacrylamide-gel electrophoresis. The enzyme was activated by ATP and ADP, and inhibited by Pi. When AMP was used as substrate, the velocity/substrate-concentration plot was sigmoidal. ATP or ADP changed the plot to hyperbolic and decreased S0.5. Pi increased both the sigmoidicity of the plot and S0.5. When IMP was used as substrate, the velocity/substrate plot w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(52 citation statements)
references
References 24 publications
(19 reference statements)
4
48
0
Order By: Relevance
“…In our study we found that the sequential elution of glycoproteins from the concanavalin-A -Sepharose column by two competing sugars (methyl a-D-glucoside and methyl a-D-mannoside) permitted a considerable increase in the degree of purification of the 5'-nucleotidase. Hence, the enrichment factor of our preparation is higher than that obtained from rat liver [13], rat heart [20], chicken liver [50], bovine brain [15] or human placenta [48] enzymes. Our results suggest that the bovine cytosolic 5'-nucleotidase is a heterodimeric protein of about 130 kDa and differs in its structure from the membrane 5'-nucleotidase [30] which is a homodimeric protein (140 kDa).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study we found that the sequential elution of glycoproteins from the concanavalin-A -Sepharose column by two competing sugars (methyl a-D-glucoside and methyl a-D-mannoside) permitted a considerable increase in the degree of purification of the 5'-nucleotidase. Hence, the enrichment factor of our preparation is higher than that obtained from rat liver [13], rat heart [20], chicken liver [50], bovine brain [15] or human placenta [48] enzymes. Our results suggest that the bovine cytosolic 5'-nucleotidase is a heterodimeric protein of about 130 kDa and differs in its structure from the membrane 5'-nucleotidase [30] which is a homodimeric protein (140 kDa).…”
Section: Discussionmentioning
confidence: 99%
“…The first one has the pyrimidine nucleotides as preferential substrates and the pH optimum of its activity occurs in a range between 7.5 and 9; the bovine liver and the human placental [48] enzymes belong to this group. The second one, including rat heart, and rat and chicken liver enzymes [13,14,20,511, is characterized by a maximal activity around pH 6.5 and a preferential affinity for the purine nucleotides and especially IMP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,34 Although ecto-5'-nucleotidase activity is affected by several neurohumoral and metabolic factors, 35 we measured 5'-nucleotidase in vitro, so it is likely that the active site of 5'-nucleotidase is directly affected by AICA riboside.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10]35 Adenosine administered even after the onset of reperfusion attenuates the ischemia and reperfusion injury in the dogs, 9,10 although beneficial effects of adenosine administered during reperfusion may depend on the animal species and the duration of ischemia. 36,37 AICA riboside administered after the onset of myocardial ischemia did not improve the contractile dysfunction in the dogs.…”
Section: Effects Of Augmented Adenosine Release Due To Aica Riboside mentioning
confidence: 99%